Impact of a sport-specific nutrition education program on knowledge and eating disorder risk in youth competitive climbers: a pilot study - Quesada, Aaron; Pablos, Ana; Drehmer, Eraci (Frontiers in Nutrition, 2026)
IntroductionSport climbing has gained popularity among youth athletes, raising concerns about eating disorders (ED) and relative energy deficiency in sport (RED-S). Although nutritional education has shown promise in preventing ED risk, its application to young climbers remains understudied. This pilot study evaluates the impact of a tailored nutrition education program, NUTYES (“NUTrición Y EScalada”: Nutrition and Climbing), on nutritional knowledge and ED risk in competitive youth climbers, providing effect size estimates to inform future definitive trials.MethodsTwenty-three young climbers (categories U-14 and U-16, representing athletes under 14 and under 16 years of age, respectively) participated in a prospective, parallel-group pilot study. Participants were allocated to either the intervention group (IG; n = 11) or control group (CG; n = 12). Anthropometric measurements (ISAK), nutritional knowledge (GeSNK), and ED risk (EAT-26) were assessed before and after an 8-week intervention consisting of seven 2-h educational sessions focused on climbing-specific nutrition needs.ResultsPost-intervention, the IG demonstrated exceptionally large improvements in sport-specific nutrition knowledge (p = 0.013; d = 1.37; 95% CI: 0.40–2.33) and total nutrition knowledge (p = 0.012; d = 1.15; 95% CI: 0.22–2.09), with significant between-group differences in change scores. General nutrition knowledge showed a large effect approaching significance (p = 0.073; d = 0.89; 95% CI: −0.02-1.80). No significant changes in ED risk were observed (p = 0.227), though a moderate effect size was detected (d = 0.58; 95% CI: −0.30-1.47) with limited statistical power (44%).DiscussionBrief sport-specific nutrition education produced exceptionally large improvements in nutritional knowledge among young climbers, with effect sizes substantially exceeding typical educational interventions in adolescent populations. While eating disorder risk showed no significant changes, the moderate effect observed suggests meaningful impacts may remain undetected due to limited statistical power and low baseline risk. These findings support the feasibility and preliminary efficacy of the NUTYES program, providing robust effect size estimates to inform future definitive trials requiring larger sample sizes (50–60 participants per group) to adequately assess eating disorder prevention outcomes.